Being a Human : Adventures in 40,000 Years of Consciousness - Foster, Charles (London Profile Books, 2021)
"A radically immersive exploration of three pivotal moments in the evolution of human consciousness, asking what kinds of creatures humans were, are, and might yet be"--
Include Illustrations and References
Keywords: Consciousness